CONTEXTUAL LEARNING IN A COMPETENCY-BASED APPROACH TO STUDYING THE SUBJECT OF OBSTETRICS AND GYNECOLOGY - Parvizi N.I (Scholar Express Journals, 2026)
Competency-based medical education emphasizes integrating theoretical knowledge with professional skills through active learning methods such as contextual, problem- and case-based learning. This study explores the implementation of contextual learning in the obstetrics and gynecology curriculum, showing how simulation, business games, and clinical problem-solving enhance clinical reasoning, communication, and professional competence. Results indicate that contextual activities foster independent decision-making and readiness for clinical practice. These findings support the broader use of contextual learning in medical education to strengthen professional development.
Keywords: competency-based education; contextual learning; obstetrics and gynecology